The Turn in Social Investigations of Scientific Knowledge. - Markova, Lyudmila A. (Russian Studies in Philosophy, 2017)
Recognizing the necessary social aspects of scientific knowledge leads to a serious shift in the analysis of science. Whereas until recently the study of scientific knowledge in terms of its social qualities began with its logical structure, today the primary focuses of analysis are the human brain, the material carrier of computer programs, the economic relations in the society of commodity production, and so forth. All of this is not science, but is involved in the production of new knowledge. The boundary between the spiritual and the material, between the scientific and nonscientific is blurred. To study this phenomenon, the vector of research shifts: social qualities are not sought in scientific knowledge, but the external world of non-science exhibits signs of the presence of the spiritual in the form of emerging scientific knowledge.